Pengaruh Kombinasi Tanaman Kehutanan Dan Pertanian (Agroforestri) Terhadap Laju Infiltrasi Di Sub-DAS Mandar: The Effect of a Combination Of Forestry And Agricultural Crops (Agroforestry) on Infiltration Rate In The Mandar Sub-Watershed - Rosmaeni Rosmaeni rosmaeni; Nurmaranti Alim Nurmaranti Alim; Tri Utami Ramadhani Tri Utami Ramadhani (Universitas Hasanuddin, 2026)
Changes in forest land use trigger watershed hydrological degradation in the form of increased surface runoff. This study examines the effect of agroforestry vegetation combinations on infiltration rates in the Mandar Sub-watershed on three types of cover: Falcataria moluccana + Coffea sp, Gmelina arborea + Coffea sp., and Gmelina arborea + Gliricidia sepium. Infiltration rates were measured in-situ using a double ring infiltrometer at 10-minute intervals and modeled using the Horton equation. Soil physical characteristics (bulk density, particle density, porosity, permeability, organic matter, and texture) were analyzed by taking intact soil samples. The analysis results showed that the average infiltration rate of the Falcataria moluccana + Coffea sp. combination reached 14,65 cm/hour (fast category), surpassing Gmelina arborea + Coffea sp. (11,71 cm/hour) and Gmelina arborea + Gliricidia sepium (11.69 cm/hour) which were categorized as rather fast. Soil physical properties significantly influence infiltration capacity, with Pearson correlation analysis showing a strong positive linear relationship between permeability (r = 0,979), porosity (r = 0,972), and sand content (r = 0,659).